A magnetism/laser-auxiliary cascaded drug delivery to pulmonary carcinoma - Jialiang Lin; Qingqing Yin; Binlong Chen; Haoran Zhang; Dong Mei; Jijun Fu; Bing He; Hua Zhang; Wenbing Dai; Xueqing Wang; Yiguang Wang; Qiang Zhang (Elsevier, 2020)
Although high-efficiency targeted delivery is investigated for years, the efficiency of tumor targeting seems still a hard core to smash. To overcome this problem, we design a three-step delivery strategy based on streptavidin-biotin interaction with the help of c(RGDfK), magnetic fields and lasers. The ultrasmall superparamagnetic iron oxide nanoparticles (USIONPs) modified with c(RGDfK) and biotin are delivered at step 1, followed by streptavidin and the doxorubicin (Dox) loaded nanosystems conjugated with biotin at steps 2 and 3, respectively. The delivery systems were proved to be efficient on A549 cells. The co-localization of signal for each step revealed the targeting mechanism. The external magnetic field could further amplify the endocytosis of USPIONs based on c(RGDfK), and magnify the uptake distinctions among different test groups. Based on photoacoustic imaging, laser-heating treatment could enhance the permeability of tumor venous blood vessels and change the insufficient blood flow in cancer. Then, it was noticed in vivo that only three-step delivery with laser-heating and magnetic fields realized the highest tumor distribution of nanosystem. Finally, the magnetism/laser-auxiliary cascaded delivery exhibited the best antitumor efficacy. Generally, this study demonstrated the necessity of combining physical, biological and chemical means of targeting.